Studi Literatur Terhadap Kebijakan Investasi Berbasis Lingkungan Hidup pada Pembangunan Kota Surabaya - Prikafais, Elfayasa; Sinardi, Gideon Verrel (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Sustainable development policies are a growing challenge in the city of Surabaya. Development that is expected to support social, cultural, and economic activities must be in line with sustainable development as determined by the government. The purpose of this research is to understand the role of the federal government, local government, and other stakeholders in developing investment strategies to make Surabaya a sustainable city. This study uses a literature study method and a descriptive-qualitative approach. The results of this study show that, as a city experiencing urbanization, Surabaya is aware of the value of sustainable development. Through GPSP, the regional government of Surabaya is working with UCLG-ASPAC to solve urbanization problems. Many policymakers from regional, national, and international levels were involved in the GPSP, which started in 2016. The project implemented three methods in its implementation: multi-stakeholder participation in design and development; utilization of new information; and implementation of project development as a pilot. In this initiative, the Surabaya City Government has a significant role and position. A sustainable city must consider a number of factors, including government, the socio-political ecosystem, and the environment.